Susan O'Neill's Full Non-breathing Stroke at 65 m of Her 200 m Butterfly Gold Medal Race at the Atlanta Olympic Games 1996 - Rushall, B. S. (1999)
Video pictures (16 frames) and the appropriate technical/ biomechanical explanations for Susan O'Neill's Full Non-breathing Stroke at 65 m of Her 200 m Butterfly Gold Medal Race at the Atlanta Olympic Games 1996. Despite the mentioned theoretical critiques, Susan O'Neill is a great swimmer of this stroke.